Motivation and emotion in the EFL learning experience of Romanian adolescent students: Two contrasting cases - Pavelescu, Liana Maria (Studies in Second Language Learning and Teaching, 2019)
The aim of this study was to investigate the language learning motivation of two EFL teenage students in Romania and the link between motivation and the emotional dimensions of these adolescents’ learning experiences. While language learning motivation has been widely researched, its relationship with emotion in the learning experience has not been examined in depth thus far. To gain deep insight into this relationship, the present study used various qualitative methods: a written task, multiple semi-structured interviews with the students and their teachers, and prolonged lesson observation. The findings showed that the learners’ motivation and emotions were closely intertwined in their learning experiences in idiosyncratic ways. Mika (pseudonym) experienced the prevalent emotion of love of English and was a highly motivated learner. In her out-of-class learning experience, her motivation was linked to her emotions towards her favorite singer. In her classroom learning experience, her motivation was shaped by her teacher’s encouragement and support. Kate (pseudonym) did not reportedly experience a dominant emotion towards English and had a rather weak motivation. The absence of an expressed dominant emotion towards English was linked to her classroom learning experience before high school, namely to her teacher’s lack of encouragement, which hindered her motivation. By focusing on two contrasting cases of learners, this study has foregrounded the role of the emotional aspects of the language learning experience in shaping motivation, showing how strong positive emotions enhance and sustain motivation and how the lack of such emotions hinders motivation.